'n Struktureel-historiese eksegese van Habakuk 1:2-2:4 - SD Snyman (Acta Theologica)
In this article Hab 1:2-2:4 is subjected to a structural-historical exegesis. This means that both the text intern aspects (demarcation of the pericope, text critical matters and a structural analysis) and the text extern aspects (Gattung, Sitz im Leben, tradition material and redaction critical matters) are investigated. The aim is to aid a literary analysis of the text with a historical dimension. In the end attention is also paid to the theology of Hab 1:2-2:4.